OPTIMIZATION AND IN VIVO EVALUATION OF MESALAMINE pH DEPENDENT COATED PELLETS FOR PROMISING ILEOCECAL TARGETING - Gangurde, Hemant H; Chordiya, Mayur Ashoka; Tamizharasi, S.; Sivakumar, T. (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
The present research is a challenge to design, optimized and evaluates mesalamine loaded burst release pH dependent coated pellets for possible ileo-cecal targeting to treat effectively Crohnâs disease. The novelty of this formulation is to release drug specifically and instantly in ileo-cecal region where the chances of Crohnâs disease is more frequent, without being released in upper gastrointestinal tract. Preliminary experimental batches are studied for micromeritic properties and in-vitro drug release. FormulationÂ showed desirable lag time of 5h and dissolution profile were further optimized by applying 32 full factorial design to study the effect of extent of coating (% w/w) Eudragit S100 and croscarmellose sodium over drug layered pellets. The regression equation generated for Q300 (lag time of 5h) = +5.72-31.97*A+0.82*B-0.49*A*B+26.36*A2-0.15*B2 and for Q390 (90% of drug release at pH7.2 within 90 minutes after lag time) = +84.63- 40.09*A+4.62*B. The drug release data of optimized formulation were close to that predicted by the model. Various kinetic models were applied to the all optimized batches. In vivo evaluation of optimized formulations was performed to assess macroscopic, microscopic and biochemical parameters in rats and performed. The present study demonstrates that the mesalamine enteric coated pellets successfully targeted at ileo-cecal region.Key words: Mesalamine, pulsatile, ileo-cecal targeting, celpheres, Croscarmellose sodium, eudragit S100